VERDICT OFF (DEATH PENALTY) FOR THE DRUG OFFENDER CRIME IN PERSPECTIVE OF ISLAMIC EDUCATION - Muhammad Tisna Nugraha (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This paper raises the issue of the death penalty for drug-crime actors in Islamic education perspective, especially when the President Joko Widodo refused to pardon the actors at the beginning of his reign. Although the execution was likely contrary to the wishes of human right instigators, but on the other hand, such punishment is one vehicle in providing education to the citizens as well as the efforts to actualize the law enforcement in Indonesia. The implementation of the death sentence does not touch directly the scope of formal education in Indonesia. However, this is where the emerging hope and the search for enlightenment of such punishment is seen from the eyes of Islamic education which has applied the concept of reward and punishment in its system. Thus, through this paper, it is expected that educators can assist in bridging the imposition of a death sentence as an attempt to form good citizens.